Relationship between Teacher Commitment to Students Learning Needs and Level of Students’ Discipline in Public Secondary Schools in Naivasha Sub-County, Kenya. - Mwaniki, Goodeve S.K; Kiumi, Prof. J. Kanjogu; Ngunjiri3, Dr. M. (International Journal of Scientific Research and Management (IJSRM), 2018)
The purpose of this study was to assess the relationship between teacher commitment to students learning needs and level of students’ discipline in public secondary schools in Naivasha sub-county, Kenya. The study targeted a total of 197 respondents (constituting 28 head teachers and 169 teachers). A total of 195 respondents participated in the study (169 teachers and 26 principals) participated giving a response rate of 99%. Purposive sampling technique was used to sample head teachers while Krejcie and Morgan’s (1970) table for determining sample size for teachers. Questionnaires were used as instrument for data collection. SPSS was used to analyze the data where both descriptive and inferential statistics were used. The analyzed data were presented in terms of graphs and tables. The results showed that there was a significant positive relationship between teacher commitment to students learning needs and level of students’ discipline (r = .271, p = .000). Therefore, the null hypothesis that there was no significant relationship between teacher commitment to students learning needs and level of students’ discipline was rejected at .05 level of confidence. The study therefore concluded that teacher commitment to students learning needs influences students’ discipline in secondary schools in Naivasha sub-county. It was recommended that teachers should be more committed to meeting the students’ learning needs. This can be achieved through holding discussions with parents on their children’s academic performance and character development.